2012
DOI: 10.1038/jid.2011.461
|View full text |Cite
|
Sign up to set email alerts
|

Hydroa Vacciniforme Is Associated with Increased Numbers of Epstein–Barr Virus–Infected γδT Cells

Abstract: Hydroa vacciniforme (HV) is a rare photosensitivity disorder of childhood associated with Epstein-Barr virus (EBV)(+) T-cell infiltration. We have summarized clinical manifestations of HV, and analyzed EBV(+) T-cell subsets as well as EBV DNA load in lymphocyte fractions, in comparison with hypersensitivity to mosquito bites (HMB), an EBV-associated T/natural killer (NK) lymphoproliferative disorder. We found that 31 of 33 (93.9%) HV lesions were composed of EBV(+) T cells and reactive EBV(-) cytotoxic T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 18 publications
2
63
0
3
Order By: Relevance
“…This observation accords with other recent reports. (43,44) The cd T cells are the major T cell population in the skin and mucosal epithelium. The cd T cells secrete various cytokines and have cytolytic properties.…”
Section: Discussionmentioning
confidence: 99%
“…This observation accords with other recent reports. (43,44) The cd T cells are the major T cell population in the skin and mucosal epithelium. The cd T cells secrete various cytokines and have cytolytic properties.…”
Section: Discussionmentioning
confidence: 99%
“…15 Recently it has been reported that HV and/or HVLL are associated with increased numbers of EBV-infected gd T cells in peripheral blood. 24,30,31 Kimura et al 24 demonstrated that the EBV-infected cells in peripheral blood in almost half of HVLL patients (6 of 13 cases) were gd T cells. Nevertheless, in none of Case CD3 CD4 CD8 TIA-1 CD56 CD30 BF1 EBER LMP EBNA2 TCR-d TCR-g Lineage BLOOD, 31 OCTOBER 2013 x VOLUME 122, NUMBER 18 HYDROA VACCINIFORME-LIKE LYMPHOMA 3107…”
Section: Differences Between Patients With a T-cell And Nk-cell Phenomentioning
confidence: 99%
“…Die histopathologische Untersuchung zeigt eine epidermale Nekrose mit intraepidermaler Blasenbildung. Für diese Verläufe ist eine Assoziation mit einer latenten oder chronisch aktiven EBV-Infektion gut dokumentiert [9,10]. Zudem ist eine Beteiligung von Mundschleimhaut, Gastrointestinaltrakt und Auge beobachtet worden [5,8].…”
Section: Kommentarunclassified